2017
DOI: 10.2147/jn.s125567
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reduces hippocampal neuron apoptosis and JNK-3 phosphorylation in rats with Aβ-induced Alzheimer's disease: protecting spatial learning and memory

Abstract: Amyloid-β peptide (Aβ) toxicity in Alzheimer's disease (AD) is associated with the c-Jun N-terminal kinase (JNK) signaling pathway. Curcumin may prevent Aβ fiber formation, slowing AD progression. A model of AD was established in 32 Sprague Dawley rats by injection of 10 μg Aβ 1-40 into the right hippocampus. Saline was used in sham control (n=16). Sixteen AD model rats received 300 mg/kg curcumin and another 16 received saline daily for 7 days. Spatial learning and memory were assessed using a Morris water ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…With the administration of curcumin, these cytokines were downregulated via the JNK/NF-κB/Akt pathway [ 87 , 122 ]. Similarly, Wang et al [ 123 ] showed that curcumin inhibited JNK-3 phosphorylation. Karlstetter et al [ 104 ] inhibited LPS-induced cyclooxygenase-2 (COX-2) by administration of curcumin.…”
Section: Curcuminmentioning
confidence: 95%
“…With the administration of curcumin, these cytokines were downregulated via the JNK/NF-κB/Akt pathway [ 87 , 122 ]. Similarly, Wang et al [ 123 ] showed that curcumin inhibited JNK-3 phosphorylation. Karlstetter et al [ 104 ] inhibited LPS-induced cyclooxygenase-2 (COX-2) by administration of curcumin.…”
Section: Curcuminmentioning
confidence: 95%
“…The toxicity of the amyloid-β peptide damages spatial learning and memory through the c-Jun N-terminal kinase (JNK) signaling pathway in AD. After treating with curcumin, AD rats show restored spatial learning and memory deficits, and JNK-3 phosphorylation is inhibited [ 141 ]. In mice with AD, active avoidance and locomotor activity are improved by curcumin, which protects against neurodegeneration [ 142 ].…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%
“…Curcumin was shown to affect protein kinase modulation, such as Akt [ 32 ], JNK [ 33 ], and GSK-3β [ 34 ]. Since protein kinase has a crucial role in protein tau phosphorylation, it may explain why tau protein level was significantly decreased in both treatment group.…”
Section: Discussionmentioning
confidence: 99%